One-dimensional TiO2 nanotube–based photocatalysts: enhanced performance by site-selective decoration - Zhou, Xuemei; Schmuki, Patrik (Surface Science of Photocatalysis, 2020)
Titanium dioxide (TiO2) is the most investigated semiconductor in photocatalysis, but the photocatalytic performance can be further improved by rational design of the material as nanostructure with special surface and structural properties. In this chapter, we discuss methods for site-selective decoration of anodic TiO2 nanotube (NT) arrays, particularly to introduce stable defects and investigate the mechanism for enhanced activity and stability of these noble metal–free photocatalysts. The investigated methods include proton implantation and nitrogen implantation into the TiO2 NTs and decoration of alternative cocatalysts (e.g., molybdenum-based cocatalysts). Such modification on TiO2 NT layers leads to the creation of efficient photocatalysts for H2 evolution, which is ascribed to the synergistic effect of light harvesting by TiO2 NTs coupled with cocatalytic centers atop the tube layers. The described methods for selective decoration of TiO2 NTs can be further extended and potentially applied to the activation of a range of one-dimensional (1D) semiconductor materials.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Anodic nanotube; H; Noble metal free; Photocatalysis; TiO